Upregulation of Endocan by Epstein-Barr Virus Latent Membrane Protein 1 and Its Clinical Significance in Nasopharyngeal Carcinoma - Yu, Ping-Hung (Public Library of Science, 2013)
Endocan (or called Esm-1) has been shown to have tumorigenic activities and its expression is associated with poor prognosis in various cancers. Latent membrane protein 1 (LMP1) is an Epstein-Barr virus (EBV)-encoded oncoprotein and has been shown to play an important role in the pathogenesis of EBV-associated nasopharyngeal carcinoma (NPC). To further understand the role of LMP1 in the pathogenesis of NPC, microarray analysis of LMP1-regulated genes in epithelial cells was performed. We found that endocan was one of the major cellular genes upregulated by LMP1. This induction of endocan by LMP1 was confirmed in several epithelial cell lines including an NPC cell line. Upregulation of endocan by LMP1 was found to be mediated through the CTAR1 and CTAR2 domains of LMP1 and through the LMP1-activated NF-κB, MEK-ERK and JNK signaling pathways. To study whether endocan was expressed in NPC and whether endocan expression was associated with LMP1 expression in NPC, the expression of endocan and LMP1 in tumor tissues from 42 NPC patients was evaluated by immunohistochemistry. Expression of endocan was found in 52% of NPC specimens. Significant correlation between LMP1 and endocan expression was observed (p<0.0001). Moreover, NPC patients with endocan expression were found to have a shorter survival than NPC patients without endocan expression (p=0.0104, log-rank test). Univariate and Multivariate analyses revealed that endocan was a potential prognostic factor for NPC. Finally, we demonstrated that endocan could stimulate the migration and invasion ability of endothelial cells and this activity of endocan was dependent on the glycan moiety and the phenylalanine-rich region of endocan. Together, these studies not only identify a new molecular marker that may predict the survival of NPC patients but also provide a new insight to the pathogenesis of NPC.